Kualitas semen dan produksi semen beku pada bangsa sapi dan bulan penampungan yang berbeda - Rahmawati, Mita Ayu; Susilawati, Trinil; Ihsan, M. Nur (Faculty of Animal Science, Universitas Brawijaya, 2015)
The purpose of this research was to determine semen quality and frozen semen production of beef cattle at different month collection in Lembang Artificial Insemination Center. Beef cattle strain that used for this research are Aceh, Angus, Brahman, Limousine, Madura, Ongole and Simmental. The research parameter included semen volume, pH, motility of spermatozoa, concentration of spermatozoa, number of spermatozoa, number of spermatozoa motil and number of frozen semen straw. The method of this research using factorial completely Randomized Design and each had 3 replication per treatment. The different of beef cattle have given a significant effect of semen volume (P<0.01), mortility of spermatozoa (P<0.01), concentration of spermatozoa (P<0.01), number of spermatozoa (P<0.01), number of spermatozoa motil (P<0.01) and pH (P>0.05). Different month collection have a significant influence of semen volume (P<0.01), pH (P<0.05), motility of spermatozoa (P<0.01), concentration of spermatozoa (P<0.01), number of spermatozoa (P<0.01), number of spermatozoa motil (P<0.01). Interaction between breed of beef cattle and different month of collection have given a significant influence of semen volume (P<0.01), motility spermatozoa (P<0.01), concentration spermatozoa (P<0.05) and number of spermatozoa motil (P<0.01). Keywords: sperm motility, concentration, number of motile spermatozoa